Development of a prototype for sensing bone-implant interface - Peres, Inês Simões (2020)
Over the last few years there has been an increase in the number of arthroplasties performed worldwide. With the growing number of young patients performing this surgery, new technologies are required to evaluate the bone-implant interface in order to avoid revision surgeries. The present work aims to develop a prototype for sensing the bone-implant interface for multifunctional instrumented/bioelectronic implants: the network-based cosurface capacitive system with ability to be extracorporeally controlled by clinicians. This prototype is composed by both hardware and software components. The hardware can also be seen as the data acquisition system and the software is the monitor and the control system. Considering that the societal scenario did not allow the manufacture of this new system prototype, the hardware was only designed for future implementation and validation. The software is a web application that allows the clinician to monitor and control the data acquisition system. For the development of the web application it was used Django, python, HTML5, CSS, and the storage and management of data were performed with MySQL. In order to assess its performance, different simulation tests were performed: (i) monitoring tests using random bone-implant interface states, in which capacitance data was generated from a polynomial function that characterizes the average capacitance change for different bone-implant bonding states; (ii) monitoring tests simulating an increasing bonding scenario. Through the web application it is possible to analyse the data collected from the data acquisition system in two dimensional plots or three dimensional plots. This software solution was also designed to allow downloading the data to an Excel file to give the user the possibility to perform different analyses related boneimplant interface state. The project for the data acquisition system is constituted by a Raspberry Pi, an I2C multiplexer, a capacitor-to-digital converter (EVAL AD-7746), and the sensing technology. The Raspberry Pi is responsible for the TCP-IP communication with the monitoring system and the I2C communication with the capacitor-to-digital converter through the I2C multiplexer. It is also responsible for saving data in the correct database. The capacitor-to-digital converter acquires the data from the sensing technology, which is based on three different printed circuit boards, containing twelve capacitors. Thus, it is intended to prove that with a sensing system comprising a network of cosurface capacitors it is possible to acquire bone-implant interface bonding during the daily life of patients, including region and magnitude debonding data